Differences in anthropometric characteristics among junior soccer and handball players - Arifi, F.; Bjelica, D.; Masanovic, B. (SportMont, 2019)
The aim of this study was to obtain the relevant knowledge about signifi cant diff erences in some anthropometric characteristics of junior soccer and handball players. The sample included 40 male subjects divided into two subsamples. The first subsample included 25 subjects, who train in the junior selection in the Football club Vojvodina from Novi Sad, while the other subsample included 15 subjects who train in the junior selection in the Handball club Vrbas, from Vrbas. The variables sample included 20 anthropometric measures that defi ned longitudinal and transversal dimensionality of skeleton, volume and mass of the body, and subcutaneous adipose tissue. The results is analysed in a statistical procedure marked as a significance testing of two arithmetic means of the independent samples, a t-test at the level of signifi cance of p<0.05. Based on the result, it was concluded that significant diff erences occur in wrist diameter, ankle joint diameter, upper arm circumference (min), upper arm circumference (max), lower leg circumference (max), upper arm skinfolf, lower arm skinfold, thigh skinfold, calf skinfold, chest skinfold and abdomen skinfold, while the significant diff erence does not occur in body height, bodyweight, elbow diameter, knee diameter, lower arm circumference (min), lower arm circumference (max), upper leg circumference (min), upper leg circumference (max), and lower leg circumference (min).